The use of systemic ozone therapy in patients with acne - F. N. Taimazova; V. T. Bazaev; O. V. Dashevskaia; D. G. Dzhavaeva (Кубанский научный медицинский вестник, 2014)
It was stadied the efficiency of complex treatment of patients with acne treated with systemozone therapy. We obser ved 90 patients (47 men and 43 women) with mild to moderate form of acne between the ages of 18 to 32 years with a dis ease duration of 1-5 years. Patients of the study group (n = 45, from which the 21 with mild acne, 24 - with moderate) rece ived retinol palmitate to 200,000 units per day for 2 months., Essenciale Forte 1 tablet 3 times a day for 2 months., zinc, 1 tab. day 1 month., Ascorutinum 1 tab. 3 times a day - 1 month., Topical disinfectants and antibiotics (2% salicylic rubbi ng alcohol and 0,05% chlorhexidine bigluconate for 2-3 months. Ointment «Fucidinum» - 1 month., Then «Baziron A» - 2 months.) and systemic ozone therapy. The control group n = 45 (22 patients - with a mild form of acne, 23 with moderat e) received similar treatment except for ozone. The use of ozone in the treatment of acne has led to a shortening of the du ration of treatment, an increase in the duration of remission, as well as a significant decrease in lipid peroxidation (LPO) -hydroperoxides and malondialdehyde, while increasing the antioxidant defense (AOD) - catalase.